Towards the sensory nature of the carotid body: Hering, De Castro and Heymans - De Castro, Fernando (Frontiers in Neuroanatomy, 2009)
The carotid body or glomus caroticum is a chemosensory organ bilaterally located between the external and internal carotid arteries. Although known by anatomists since the report included by Von Haller and Taube in the mid XVIIIth century, its detailed study started the first quarter of the XXth. The Austro-German physiologist Heinrich E. Hering studied the cardio-respiratory reflexes searched for the anatomical basis of this reflex in the carotid sinus, while the Ghent School leaded by the physio-pharmacologists Jean-François Heymans and his son Corneille focussed in the cardio-aortic reflexogenic region. In 1925, Fernando De Castro, one of the youngest and more brilliant disciples of Santiago Ramón y Cajal at the Laboratorio de Investigaciones Biológicas (Madrid, Spain), profited from some original novelties in histological procedures to study the fine structure and innervation of the carotid body. De Castro unravelled them in a series of scientific papers published between 1926 and 1929, which became the basis to consider the carotid body as a sensory receptor (or chemoreceptor) to detect the chemical changes in the composition of the blood. Indeed, this was the first description of arterial chemoreceptors. Impressed by the novelty and implications of the work of De Castro, Corneille Heymans invited the Spanish neurologist to visit Ghent on two occasions (1929 and 1932), where both performed experiences together. Shortly after, Heymans visited De Castro at the Instituto Cajal (Madrid). From 1932-33, Corneille Heymans focused all his attention on the carotid body his physiological demonstration of De Castro’s hypothesis regarding chemoreceptors was awarded with the Nobel Prize in Physiology or Medicine in 1938, just when Spain was immersed in its catastrophic Civil War.